Thermodynamic modeling of deoxidation products and inclusion chemistry in Mn/Si killed tire-cord steel - Prasad A.D.; Sankaranarayanan S.R. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The present work deals with thermodynamic modeling of oxide systems, in the context of slags and inclusions in steelmaking. The work has emphasis on oxides encountered during the production of tire - cord steel. Control of inclusion chemistry and variation in eutectic temperature and eutectic composition of MnOAl2O3- SiO2 slag system have been studied, using Thermo-CalcR software. Relatively low liquidus temperatures are obtained for ratio of MnO/SiO2 = 0.5 - 1.5 and Al2O3 content from 10 - 20 mass%. It has been observed that the addition of Alumina leads to further increase in the liquidus temperature. The stability of inclusions is analyzed in terms of free energy values of related slag systems; and an appropriate minimum of Gibbs free energy value of slag phase observed at around 50 ppm of Oxygen. The observations could not be verified using thermodynamic experiments, but have been compared with findings in the open literature.